Public Involvement in NHS Inquiries. Issue 2 (21st May 2019) - Carlyle, Ruth
Abstract: Opportunities for engaging the public have changed over the fifty years since the inquiry into the Ely Hospital, Cardiff. NHS inquiries, and inquiries more widely, tend to be called where events have led to public concern and loss of public confidence. Involvement of the public could therefore be assumed to form a part of restoring that public confidence. This paper explores the mechanisms for public involvement in NHS inquiries over the past fifty years, assessing the roles played by the public. It uses the framework outlined by Geoffrey Howe to examine how members of the public have been involved in four NHS inquiries. Findings suggest that the roles and mechanisms have varied, but that understanding the extent of public involvement is a dimension to assessing each of the potential functions of an NHS inquiry.